Records in contexts – a conceptual model for archival description (RIC-CM): análise da proposta de um padrão internacional integrado de descrição arquivística - Moraes, Humberto Antônio Ribas (Universidade Federal de São Carlos, 2018)
In view of the applications of information and communication technology in processes of archival description, interoperability and cooperation between registries, there is a need to re-evaluate the internationally recognized standards of archival description. To this end, the International Council on Archives proposes Records in Contexts, a conceptual model of archival description identified as RiC-CM. Faced with the question "where in the RIC-CM meets archival description requirements according to public consultation the archival community?" the general objective of the research is to explore the adherence of the RiC-CM to the archival description requirements indicated by the archival community and to examine the conceptual, methodological and practical aspects of the archival description; explore the RiC-CM; analyze the AtoM software; evaluate the manifestations of the archival community in response to the public consultation with RiC-CM. As methodological procedures, the qualitative approach is applied, with an exploratory and descriptive purpose and uses bibliographic and documentary procedures. As a result, the RiC-CM needs a considerable amount of adjustments in the approaches to methodology, project development, inclusion, transparency, comprehensiveness and technology, although the ICA initiative proposes a fill a gap regarding the standardization of archival description be commendable. It is understood that the RiC, despite all the criticisms, is making possible a discussion about the current ICA norms and awakens to the necessity of having a standard that, at world level, meets the needs of archivists, regardless of language or country, and which aims at the application of the linked open data.
Records in contexts - the conceptual model for archival description (RIC-CM): analysis of the proposal for an integrated international pattern of archivisian description
Keywords: Records in Contexts; Descrição arquivística; RiC-CM; AtoM; Modelo conceitual; Records in contexts; Archival description; RiC-CM; AtoM; Conceptual model; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::ARQUIVOLOGIA